Significados da Felicidade nas Dimensões do Espaço Urbano - Ueda, Guilherme Shoiti (2023)
This thesis investigates the use of happiness as a guiding principle to comprehensively understand the production of urban space. To do this, the concept of happiness is analyzed in different theoretical perspectives, seeking to understand how it influences human attitudes and behaviors, which determine the way spaces are built and used. In this way, connections are established between different areas of knowledge, such as philosophy, psychology, psychoanalysis, and geography, to establish a relationship between happiness and urban space. The thesis argues that this relationship is bidirectional, conceiving the city as a continuous process of deconstruction, based on the hypothesis that the contemporary conception of happiness is artificially created to satisfy the interests of capitalism, distancing the human being from the biological cycles of natural ecosystems. In this context, the role of territoriality, ethics, security and culture is also analyzed as fundamental elements for the formation of a new world view, in which ecological consciousness is internalized and can generate a cycle of happiness.